Spatial heterogeneity of global forest aboveground carbon stocks and fluxes constrained by spaceborne lidar data and mechanistic modeling - Ma, Lei (Global change biology, 2023)
© 2023 The Authors. Global Change Biology published by John Wiley & Sons Ltd.